Asesmen Bangunan Gedung Pemda Kota Palu, Donggala dan Parigi Moutong Pasca Gempa 28 September 2018 - Listiawaty, H.; Sulendra, I .K.; Hilmansyah, T. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2022)
After a strong earthquake with a magnitude of 7.4 on the Richter Scale with a hypocenter of 10 km and an epicenter of about 70 km north of Palu City, precisely in Lende Village, Sirenja District, Donggala Regency, it caused damage and collapse of buildings due to vibrations, fractures of down lifts and up lifts around the fault trajectory. Palu-Koro. Damage and failure of high-rise and non-rise buildings occurred in Palu City, Donggala City, and Parigi City. Damage to the building can be categorized as light, moderate or heavy damage, so it is deemed necessary to conduct an assessment according to the applicable requirements both on a national scale (using the Ministry of Public Works and Public Housing's 2010 form) and an international form (using a form from the World Bank). This activity aims to determine the level of damage and post-earthquake handling in the form of minor repairs, reinforcement and repair of structural and non-structural elements. There are 6 (six) main buildings in the 3 (three) areas that have been assessed to determine the category of damage and actions for rehabilitation and reconstruction. Damage to the building structure with the category of Light Damage occurred in the Palu City DPRD Office building, the Donggala Regent and DPRD Office and the Anuntaloko Parigi Hospital Inpatient Building. Those that were moderately damaged were the Palu Mayor's Office building and the Parigi Moutong DPRD office. The damaged buildings still allow for repairs and reinforcement according to the level of damage. The repair and strengthening of buildings in order to get good results must be carried out with the right method, good materials and tools and technology and carried out by experienced workers with high qualifications